Does experimentally induced pain-related fear influence central and peripheral movement preparation in healthy people and patients with low back pain?. Issue 6 (June 2020) - Schouppe, Stijn; Clauwaert, Amanda; Van Oosterwijck, Jessica; Van Damme, Stefaan; Palmans, Tanneke; Wiersema, Jan R.; Sanchis-Sanchéz, Enrique; Danneels, Lieven
Abstract : Abstract: Nonspecific chronic low back pain (CLBP) is a multifactorial disorder. Pain-related fear and altered movement preparation are considered to be key factors in the chronification process. Interactions between both have been hypothesized, but studies examining the influence of situational fear on movement preparation in low back pain (LBP) are wanting, as well as studies differentiating between recurrent LBP (RLBP) and CLBP. Therefore, this study examined whether experimentally induced pain-related fear influences movement preparation. In healthy controls (n = 32), RLBP (n = 31) and CLBP (n = 30) patients central and peripheral measures of movement preparation were assessed by concurrently measuring trunk muscle anticipatory postural adjustments (APA) with electromyography and contingent negative variation with EEG during performance of rapid arm movements. Two conditions were compared, one without (no fear) and one with (fear) possibility of painful stimulation to the back during rapid arm movements. Visual analogue scales were used to assess pain-related expectations/fear in both conditions. The experimentally induced fear of pain during movement performance led to an increase in contingent negative variation amplitude, which was similar in all 3 groups. Concerning APAs, no effects of fear were found, but group differences with generally delayed APAs in CLBP compared with controls and RLBP patients were evident. These results suggest that with fear, an attentional redirection towards more conscious central movement preparation strategies occurs. Furthermore, differences in movement preparation in patients with RLBP and CLBP exist, which could explain why patients with RLBP have more recovery capabilities than patients with CLBP. Abstract : Pain-related fear alters central, but not peripheral, movement preparation processes. Patients with recurrent and chronic low back pain have different peripheral, but not central, movement preparation.